Cohort study of oncologic emergencies in patients with head and neck cancer. Issue 6 (27th March 2017) - Reyes–Gibby, Cielito C.; Melkonian, Stephanie C.; Hanna, Ehab Y.; Yeung, Sai‐ching J.; Lu, Charles; Chambers, Mark S.; Banala, Srinivas R.; Gunn, Gary B.; Shete, Sanjay S.
ABSTRACT: Background: Treatments for head and neck squamous cell carcinoma (HNSCC) are associated with toxicities that lead to emergency department presentation. Methods: We utilized data from an ongoing prospective cohort of newly diagnosed, previously untreated patients ( N = 298) with HNSCC to evaluate the association between clinical and epidemiologic factors and risk for and frequency of emergency department presentation. Time to event was calculated from the date of treatment initiation to emergency department presentation, date of death, or current date. Frequency of emergency department presentation was the sum of emergency department visits during the follow‐up time. Results: History of hypertension, normal/underweight body mass index (BMI), and probable depression predicted increased risk for emergency department presentation. BMI and severe pain were associated with higher frequency of emergency department presentations. Conclusion: Clinical and epidemiologic factors can help predict patients with HNSCC who will present to the emergency department. Such knowledge may improve treatment‐related patient outcomes and quality of life. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1195–1204, 2017